2006
DOI: 10.1590/s0100-204x2006001000013
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity testing of corn seeds as influenced by temperature and period of storage

Abstract: -The objective of this work was to evaluate the effects of temperature (10, 20, 30, 20/10 and 30/10ºC) and period of storage on electrical conductivity (EC) in four seed lots of corn (Zea mays L.), as well as the mineral composition of the soaking solution. EC test determines indirectly the integrity of seed membrane systems, and is used for the assessment of seed vigor, because this test detects the seed deterioration process since its early phase. The research comprised determinations of water content, ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 14 publications
3
26
0
11
Order By: Relevance
“…Research has shown that seed quality is influenced by genotype, environment during seed development, and seed storage conditions (Clerkx et al, 2004;Fessel et al, 2006;Açıkgöz et al, 2013;Hampton et al, 2013;Hay et al, 2013;Uddin et al, 2013). Our results suggest significant differences in longevity could not be found between either different species of the same genus (Diplotaxis tenuifolia and D. erucoides), or different seed lots of the same species (D. tenuifolia).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that seed quality is influenced by genotype, environment during seed development, and seed storage conditions (Clerkx et al, 2004;Fessel et al, 2006;Açıkgöz et al, 2013;Hampton et al, 2013;Hay et al, 2013;Uddin et al, 2013). Our results suggest significant differences in longevity could not be found between either different species of the same genus (Diplotaxis tenuifolia and D. erucoides), or different seed lots of the same species (D. tenuifolia).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found by the present study, which wasn't able to use this variable (Ca) when analyzing seeds vigor. Whereas calcium increase was documented by Fessel et al (2006) for corn, by Fessel et al (2010) for soy seeds with high and low vigor, and by Silva et al (2012) in lots of beans with lower physiological quality.…”
Section: Resultsmentioning
confidence: 94%
“…Studies with peanut (Arachis hypogaea L.) (Vanzolini and Nakagawa, 1999b), soybean (Glycine max (L.) Merrill) (Vieira et al, 2002), corn (Zea mays L.) (Fessel et al, 2006) and cowpea (Vigna unguiculata (L.) Walp.) seeds have shown that the electrical conductivity test is suitable for evaluating a seed lot's vigour.…”
Section: Resultsmentioning
confidence: 99%